Troubleshooting Oracle performance - Antognini, Christian (Apress, 2014)
A systematic guide to diagnosing and resolving performance problems in database-backed applications involving Oracle's database engine. This second edition has been rigorously updated to cover the latest developments in Oracle Database 11g Release 2 through Oracle Database 12c. What you'll learn: Systematically identify performance problems; Configure the query optimizer to meet performance goals; Read and recognize inefficient execution plans; Minimize the impact of parsing upon performance; Optimize data access, joins, and the physical design of your database; Improve performance through parallel processing, materialized views, and result caching; Apply SQL tuning techniques such as hints, SQL profiles, stored outlines, and SQL plan baselines; Reduce inefficiencies from too much procedural code. Who this book is for: application developers and database administrators involved in troubleshooting performance problems in Oracle-based applications. --